Pedestrian Destinations and Behavior in Bandar Lampung City Center by Mode of Transportation - Haris Murwadi; Mahendra Eka Perkasa; B. Chrysvania Artemisia; Panca Indra (Jurnal Arsitektur, 2023)
A city that has a variety of destinations will attract many people to come to visit. People who visit using private vehicles have an impact on the route and increase gas emissions that can damage the environment. Reducing gas emissions in the environment needs to be done by changing transportation to transportation that does not produce gas emissions (green transportation). Destinations that go with green transportation require proper pedestrian paths. This study aims to determine which pedestrian paths are often traversed by the community and the relationship between modes of transportation and the intended destination. The research method used is qualitative with data collection carried out through the distribution of online questionnaires. Data were analyzed by correspondence analysis and clustering analysis. The findings resulting from this study are (1) Jalan Z.A. Pagar Alam and Jalan Raden-Intan are routes that have a high impact on the economy, while Jalan Imam Bonjol and Jalan Teuku Umar are routes that are often used when going to public buildings (low economy), (2) People tend to use green transportation (walking) towards public buildings, while people who use motorized vehicles tend to go to commercial areas.